Concept Development of Unmanned Ground Vehicles in Dual-Use Operations - Larsson, Sofia; Tinghall , Julia (My University, 2026)
Unmanned Ground Vehicles (UGVs) are becoming increasingly relevant in military and dual-use operations due to their ability to reduce risks for personnel and support missions in high-risk environments. Recent conflicts have demonstrated the growing need for resilient autonomous and remotely operated systems capable of supporting casualty evacuation, medical evacuation, and logistics close to the frontline. Despite rapid technological development, there remains a need for structured methods to support early-stage concept development of such systems. This thesis investigates how Systems Engineering (SE) methods can support early product development and conceptual system-level design of UGVs for dual-use and near-front operations. The study aims to identify stakeholder and user needs, define relevant operational scenarios, and develop concept proposals adapted for CasEvac, MedEvac, and logistics missions. The project was conducted through theory research, market and competitor analyses, and semi-structured interviews with stakeholders, users, and experts. A Systems Engineering approach was applied using Concept of Operations (ConOps) and Model-Based Systems Engineering (MBSE) methods to structure operational and system-level analysis. Identified requirements and operational scenarios were translated into functional system models and visualized through CAD-based concept development. The results show that modularity, adaptability, compact dimensions, and safe patient transport are key design considerations for UGVs operating in high-risk environments. Three mission-oriented concept proposals were developed and evaluated based on identified operational needs. Furthermore, the study demonstrates that Systems Engineering methods support traceability, communication, and structured decision-making during early product development. The thesis contributes with a conceptual framework and design approach for future development of resilient dual-use UGVs in evacuation and logistics operations
Keywords: Unmanned Ground Vehicles (UGV); Dual-Use Operations; CasEvac; MedEvac; Logistics; Systems Engineering (SE); Concept of Operations (ConOps)